Spaces of connection and belonging: young people's perspectives on the role of youth cafés in their lives. Issue 4 (2nd October 2018) - Brady, Bernadine; Forkan, Cormac; Moran, Lisa
ABSTRACT: A youth café is a relaxed, drug-free and alcohol-free meeting space for young people. The youth café model has become a prominent form of policy provision for young people in Ireland over the past decade, with in excess of 160 youth cafés now in operation. While the youth café model is not unique to Ireland, there has been little published research internationally on the perspectives of young people regarding the role of youth cafés in their lives. Drawing on qualitative research with 102 young people from 10 youth cafés in Ireland, this article presents findings in relation to six thematic areas: feeling supported; belonging and connection; personal and identity development; safety; alcohol and drugs; and education. The findings indicate that the attraction of the model for young people is that it respects their individualised preferences for engagement whilst providing them with a sense of ownership and connection. It is argued that the values and principles underpinning the model are instrumental in creating "care-full" spaces that enhance the well-being of children and young people.